Method for plasty of post-burn scar deformation of the hand using intraoperative balloon stretch - Madazimov Madamin Muminovich; Askhanov Zafarbek Pattakhonovich (Zien Journals, 2022)
In this article, the author proposed a method for plasticizing post-burn scarring of the hand using intraoperative balloon stretching. The effectiveness of treatment was studied in 42 patients who underwent plastic surgery using intraoperative balloon stretching of the hand tissues. The patients were divided into 2 groups: group 1 consisted of 25 and group 2 of 17 patients. 85.8% of patients in the main group had good and satisfactory results. In the comparison group, these figures were 73.3%. Based on this, the proposed method of plasticizing post-burn scarring of the hand with intraoperative balloon stretching made it possible to increase the results by 12.5%.
Keywords: Scar; post-burn deformity; intraoperative; hand